2019
DOI: 10.1111/pace.13742
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the safety of implantable cardioverter‐defibrillator reuse—A retrospective case‐control study

Abstract: Aims The safety of pacemaker reuse has been proven by numerous studies in the last two decades. With the exception of one research paper, the safety of reuse of implantable cardioverter‐defibrillators has not been properly investigated. Our aim was to establish whether resterilized implantable cardioverter‐defibrillators are as safe as new devices in relation to functionality and infection rates. Methods All the patients (n = 271) implanted with a new or a donated, used implantable cardioverter‐defibrillator (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 11 publications
1
11
0
1
Order By: Relevance
“…Our results are consistent with those of other studies that compared the clinical outcomes of new vs resterilized CIEDs [ 4 , 9 , 11–13 ]. The combined results provide persuasive evidence of the safety and efficacy of reimplantation of resterilized CIED.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our results are consistent with those of other studies that compared the clinical outcomes of new vs resterilized CIEDs [ 4 , 9 , 11–13 ]. The combined results provide persuasive evidence of the safety and efficacy of reimplantation of resterilized CIED.…”
Section: Discussionsupporting
confidence: 93%
“…Several recent studies have reported an infection rate of <5% with resterilized CIEDs, suggesting comparable risk with that of new devices ( Supplementary Table 3 ) [ 4 , 9 , 11–13 ]. In a multinational study that follows the infection outcomes of reused CIEDs that entered the prospective Heart to Heart registry, established in 2003, the rate of device infection at 2 years was 2.0% among the 1051 patients with reused CIEDs and 1.2% among 3153 patients with new devices [ 11 ].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Therefore, due to the high cost of new devices, the reuse of used CIEDs appears to be a feasible and safe option, especially when the alternative would be not having any device at all 18–20 . In the European Community there is no uniform policy regarding CIED reuse, while in Romania CIEDs are usually reused, the United Kingdom, France, Spain and Switzerland have published recommendations or prohibitions about reprocessing this type of products 21–23 . Reprocessing CIEDs for reimplantation is not allowed in the United States either, due to the risk of infection 24 .…”
Section: Introductionmentioning
confidence: 99%